Development of a new empirical correlation for steam condensation rates in the presence of air outside vertical smooth tube. (March 2018) - Fan, Guangming; Tong, Pan; Sun, Zhongning; Chen, Yitung
Highlights: Steam-air mixtures condensation outside a smooth tube were conducted. There is a negative power function relation between condensation coefficient and wall subcooling. The exponent varies with wall subcooling and total pressure. A new empirical correlation for steam-air condensation are developed. The validity of the new correlation is confirmed. Abstract: In the past several decades, experimentalists have proposed a large number of correlations to estimate steam condensation rates in the presence of noncondensable gases within free convection regime. However, these correlations are in different forms, and even express conflicting dependencies of the condensation coefficient on some parameters. This study is to aim at developing a new correlation which can faithfully reflect the complex dependencies of condensation coefficient on pressure, air mass fraction and wall subcooling. Considering that more measured data can certainly help to analyze the relationship between condensation coefficient and these parameters, total 374 sets of experimental data have been obtained. It is found that there is a negative power function relation between condensation coefficient and wall subcooling, and the exponent varies with wall subcooling and total pressure. The new correlation, covering two orders of magnitude in the condensation heat transfer coefficient, is valid for pressure ranging from 0.2 to 0.5 MPa, air mass fraction ranging from 0.1 to 0.8 and wall subcooling ranging from 10 to 70 °C. Finally, we have made comparison with experimental data obtained by other investigators which shows that the new correlation is applicative for not only steam-air condensation but also steam-nitrogen and steam-argon condensation, and it can be extended to larger scope of engineering applications.